Between assistance and misconduct: Generative AI, epistemic integrity, and the future of mathematics education research in Journal on Mathematics Education - Zulkardi; Prahmana, Rully Charitas Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
This editorial examines the role of generative artificial intelligence (GenAI) in reshaping the ecology of scholarly writing in mathematics education, with particular attention to the Journal on Mathematics Education (JME). Grounded in the Indonesian context—where most JME authors are doctoral students navigating pressures to publish in English—the piece highlights how GenAI simultaneously functions as a linguistic lifeline and a potential trap that obscures the intellectual labor of research. Drawing on JME's GenAI policy, we argue that journals must protect the core of intellectual work while acknowledging the unequal access to AI tools across institutions and regions. The editorial discusses epistemic risks such as the erasure of authors'